Relationship between principal's emotional intelligence, leadership style and teacher's organizational trust and commitment in Golestan, Iran - Mirza, Mojgan (2012)
Various studies have been done in commitment, however, only a few of them were related to educational organizations. Relatively, there is still very limited research which supports the argument that school characteristics can influence the level of teachers’ commitment. The present study therefore aims to determine the influence of the school principals’ emotional intelligence and leadership styles on development of the teachers’ trust and commitment. This study employed survey design based upon the research questions. The study was carried out among 268 school’s principals and 513 teachers in Golestan Province, Iran. The descriptive findings show average-effective functioning category for principals’ emotional intelligence. In ddition, principals exhibit a transformational leadership style. Moreover, descriptive statistics show a ranking with teachers’ trust in co-worker, trust in supervisor and trust in Stepwise Multiple Regression indicates that principal’s emotional intelligence,transformational leadership style and teacher’s trust, significantly contributed towards teacher’s commitment. Path analysis indicates an influential ranking on teacher’s commitment by principal’s emotional intelligence, transformational leadership style, and teacher’s trust, respectively. Moreover, fit indices in Structure Equation Model show that proposed model of transformational leadership style is adequately fitted to collected data of the study. Generally, the study concludes that principals’ emotional intelligence and leadership styles are important variables in explain the teacher’s trust and commitment.